Brodsky among us : a memoir - Proffer Teasley, Ellendea, 1944- (Boston : Academic Studies Press, 2017)
"A searingly personal memoir of the great Russian poet by his American friend and publisher, containing much previously unknown material about how Brodsky left Russia and how he made his way in the new world, and how, during the cold war, Americans played a crucial role in his fate"--
Pages:1 to 25; Pages:26 to 50; Pages:51 to 75; Pages:76 to 100; Pages:101 to 125; Pages:126 to 150; Pages:151 to 175; Pages:176 to 190
Print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Brodsky, Joseph, -- 1940-1996.; Brodsky, Joseph, -- 1940-1996.; Poets, Russian -- 20th century -- Biography; LITERARY CRITICISM -- Russian & Former Soviet Union; POETRY -- Russian & Former Soviet Union; Poets, Russian; BIOGRAPHY & AUTOBIOGRAPHY / General; 1900-1999; Biography; Electronic books